Interference between Rhizobium meliloti and Rhizobium trifolii nodulation genes: genetic basis of R. meliloti dominance. - Debellé, F (1988)
Transfer of an IncP plasmid carrying the Rhizobium meliloti nodFE, nodG, and nodH genes to Rhizobium trifolii enabled R. trifolii to nodulate alfalfa (Medicago sativa), the normal host of R. meliloti. Using transposon Tn5-linked mutations and in vitro-constructed deletions of the R. meliloti nodFE, nodG, and nodH genes, we showed that R. meliloti nodH was required for R. trifolii to elicit both root hair curling and nodule initiation on alfalfa and that nodH, nodFE, and nodG were required for R. trifolii to elicit infection threads in alfalfa root hairs. Interestingly, the transfer of the R. meliloti nodFE, nodG, and nodH genes to R. trifolii prevented R. trifolii from infecting and nodulating its normal host, white clover (Trifolium repens). Experiments with the mutated R. meliloti nodH, nodF, nodE, and nodG genes demonstrated that nodH, nodF, nodE, and possibly nodG have an additive effect in blocking infection and nodulation of clover.